AN EXPLORATORY STUDY ON CARICOM (CARIBBEAN COMMUNITY)- A CASE OF REGIONAL TRADE BLOC - Gupta, Shreya; Sahdev, Supriya Lamba (International Journal of Research -GRANTHAALAYAH, 2018)
The study throws light on the regional bloc CARICOM and the issues faced by the same. Secondary data has been used from journals, newspaper articles and books for analyzing the current scenario. From this paper we have learned that there are still many issues among the member countries and to resolve these issues disputes settlement mechanism similar to WTO should be followed for resolving dispute among member countries.